Aspirated oat liftings for growing calves - Robert T. Brandt Jr.; Gerry L. Kuhl; F.K. Brazle; L.R. Corah; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1990)
Feed value of aspirated oat liftings (AOL), a by-product of the oat milling industry, was evaluated by using it to replace 33, 67, or 100% of 36 lb/bu oats in a growing diet fed to heifers. Ammonia treatment of AOL was also tested. Dry matter intake and feed/gain increased linearly (P<.10) with increased AOL. Daily gains were similar for 33, 67, and 100% AOL inclusions, which were lower (P<.01) than the control (0% AOL). Despite lower performance, cheaper costs of production may be achieved with AOL depending on its price relative to other feedstuffs. Ammonia treatment of AOL had no beneficial effect on heifer performance in this study.
Keywords: Cattlemen& #x27; s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Oats; By-products; Ammoniation; Growing